Dietary Fat and Cardiovascular Disease: Ebb and Flow Over the Last Half Century - Lichtenstein, Alice H (Adv Nutr, 2019)
Dietary modification has been the cornerstone of cardiovascular disease (CVD) prevention since the middle of the last century when the American Heart Association (AHA) first issued recommendations. For the vast majority of that time the focus has been on saturated fat, with or without concomitant guidance for total or unsaturated fat. Over the past few years there has been a renewed debate about the relation between dietary saturated fat and CVD risk, prompted by a series of systematic reviews that have come to what appears to be different conclusions. This triggered a robust discourse about this controversy in the media that in turn has led to confusion in the general public. The genesis of the different conclusions among the systematic reviews has been identified in several studies on the basis of isocaloric substitution analyses. When the data were analyzed on the basis of polyunsaturated fat replacing saturated fat, there was a positive relation between dietary saturated fat and CVD. When the data were analyzed on the basis of carbohydrate replacing saturated fat, there was a null relation between dietary saturated fat and CVD. When the substitution macronutrient was not taken into consideration, the differential effects of the macronutrient substitution went unrecognized and the relations judged as null. The lack of distinction among substituted macronutrients accounted for much of what appeared to be discrepancies. Dietary guidance consistent with replacing foods high in saturated fat with foods high in unsaturated fat, first recommended more than 50 y ago, remains appropriate to this day.